Necesidad de Reformar el Código Orgánico Integral Penal con la finalidad de establecer la tipificación y penalización de la Mala Práctica Profesional Médica - Salazar Torres, Cristhel Dolores (2015)
The theme of the Civil and Criminal responsibility in health is now a matter of much discussion in our country and the world. Accountability is the obligation is to repair damage to another, provided that all three constituent elements: the existence of a specific action by subjective values (intent or negligence), damage or injury and the causal link between one and another, and that the responsibility of the physician must consider many variants, since it can analyze criminal and civil, as well as tort and contract. However, in the case of non-contractual liability for the exercise of the profession of medicine, concur in your determination, plus his own private practice factors, other public and some that transcend the realm of the concrete, such as ethical and moral precepts. Today it is no stranger in the world of medical malpractice cases in Ecuador, which at this time I have been on the increase. But also we see, and healthcare professionals affected families go unpunished which at the lack of clarity in the Organic Comprehensive Criminal Code, did not receive a penalty according to the seriousness of the facts after threatening the lives and safety of the people. Nobody asks to be infallible, that would be unrealistic, but should establish accountability when there are serious cases and proven malpractice. In medical malpractice is very difficult to achieve success on a legal claim because the lack of specific treatment in cases of medical malpractice in the Ecuadorian legal system, causes the victim of this act does not require justice. In criminal matters, medical practice has generally been typecast assimilating with crimes that exist within the Criminal Code of Integral but not treating it as a separate offense, creating a big loophole when solving these proceedings. This arises from the need for a legal response to this new reality, seeking the best way to balance the interests of patient protection affected by poor medical care. Poor performance in civil and criminal matters in cases of medical malpractice with regard to liability and application of evidence in judicial proceedings, by the legislative authorities causing increasing difficulties to determine what is the best way to punish Medical action.